Pengaruh Proses dan Variasi Fraksi Perekat Briket Antrasit Terhadap Nilai Kuat Tekan - Fadhian, Muhammad Filo; Wahyudie, Ilham Ary; Yuliyanto, Yuliyanto (Jurnal Inovasi Teknologi Terapan, 2025)
The transition away from reliance on fossil fuels is critical to fostering the development of renewable energy sources, with briquettes emerging as a particularly popular alternative. This study evaluates the effects of drying processes and variations in binder fractions on the compressive strength of anthracite briquettes. The briquettes were produced using binder fractions (water: dolomite lime) of 4:10, 4:12, 5:10, and 5:12 and subjected to mechanical pressures of 8, 9, and 10 tons with drying durations of 2, 4, and 6 days. The findings indicate that the 5:12 binder fraction achieved the highest compressive strength of 544 kPa after 6 days of drying, reflecting enhanced mechanical strength due to increased dolomite lime content. Conversely, an optimal drying time of 4 days was identified, balancing moisture reduction and briquette structural stability. This research provides valuable insights for developing high-quality briquettes as efficient and environmentally friendly renewable energy sources.